Determinant of Implanon discontinuation among women in southwest Ethiopia: unmatched case control study - Samuel Ejeta Chibsa; Kenbon Bayisa; Mustefa Adem Hussen; Bilisumamulifna Tefera Kefeni (BMC, 2023)
Abstract Background Over 4.5 million women worldwide have used Implanon. It plays an important role in reducing unwanted conceptions, lowering maternal mortality, and enhancing child survival. As a result, the availability of family planning programmes encourages women to begin using contraception and encourages women who are already using family planning to continue using it. The purpose of this study was to investigate the factors that lead to implanon cessation among women in southwest, Ethiopia. Methods A facility-based unmatched case-control study was conducted from February 01 to March 02, 2023. It included 348 participants, 174 cases, and 174 controls. The cases were selected consecutively, and the controls were selected using a systematic random sampling method. Data was collected through a structured, face-to-face interview and entered into Epi-data version 4.6 and SPSS version 25.0 for analysis. The confidence interval (CI) of 95 and the strength of the association were measured using an adjusted odds ratio. A p-value of less than 0.05 was considered statistically significant. Result Women whose husbands have formal education [AOR = 0.33, 95% CI (0.121-0.0944)], women who have been counseled individually [AOR = 3.403 (1.390-8.3.32)], women who have been counseled for less than 5 min [AOR = 3.143, 95% CI (1.303-8.046)], and women who discuss Implanon insertion with their partner [AOR = 0.289, 95% CI (0.143-0.585)] were significantly associated with Implanon discontinuation. Conclusion Implanon discontinuation was predicted by the husband's education, the number of women counselled alone, the length of counselling, a conversation with the spouse, satisfaction with the service, and implanon side effects. The health care provider should increase counselling services, especially the length of implanon pregnancy, in accordance with the national family planning recommendations, to reduce early implanon removal.